Digital Marketing Strategies, Consumer Behavior, and Competitive Advantage in the Global Business Environment - Sri Lestari (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In the era of globalization and digital transformation, digital marketing strategies have become a crucial factor in shaping consumer behavior and creating competitive advantage for companies. The development of digital technology has transformed the way companies interact with consumers and create value in an increasingly dynamic global marketplace. This study aims to analyze the relationship between digital marketing strategies, consumer behavior, and competitive advantage in the context of global business. The research method used is a descriptive qualitative approach through library research, reinforced by conceptual and comparative analysis of various academic sources and relevant industry publications. The study results indicate that effective digital marketing strategies, through the use of social media, e-commerce, data analytics, artificial intelligence and big data technologies, can increase consumer personalization, engagement, and trust. The research findings also reveal that a company's ability to adapt to increasingly data-driven changes in consumer behavior is key to building a sustainable competitive advantage. Therefore, optimizing an integrated digital marketing strategy plays a crucial role in strengthening a company's position in a competitive and evolving global marketplace.